Evaluation of maternal-fetal outcomes, clinical manifestations, prevalence and associated factors of uterine fibroids during pregnancy: a study in a tertiary care hospital - Sultana, Sabiha; Khatun, Rahima; Sultana, Tayeba; Zakiatul Husna, Umme Hafsa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Uterine fibroids, noncancerous growths arising from the smooth muscle cells of the uterus, are prevalent benign tumors in women during their reproductive years. Despite many pregnancies proceeding without complications, literature suggests an elevated risk during pregnancy, prompting the study to assess delivery modes in pregnant individuals with a fibroid uterus. The study aims to assess maternal-fetal outcomes, clinical manifestations, prevalence and associated factors of uterine fibroids during pregnancy. Methods: This cross-sectional study, conducted at Shaheed Monsur Ali Medical College, Dhaka from 2018 to 2022, involved 80 pregnant women receiving antenatal care. Before the examination, informed consent was obtained, and participants signed the informed consent form on the examination day. Inclusion criteria comprised individuals aged 21 to 40, or >40 with a gestational age between 33 to 38 weeks, having single or multiple uterine fibroids exceeding 3/4 cm in size. Informed consent was obtained, and data collection included demographics, medical history, and ultrasound reports to assess uterine fibroids, analyzed using SPSS version 20. Results: The study involving 80 patients with uterine fibroids reveals that the majority fall within the 31-35 age range, with a balanced urban-rural residency split. Muslim patients are predominant, and educational backgrounds show a nearly equal distribution between literate and illiterate individuals. Most patients have a BMI between 25-30 kg/m2 or >30 kg/m2. Submucosal fibroids are the most prevalent type (41.25%), mainly located in the fundus (33.75%). Caesarean section is the primary delivery mode (57.50%), with Fetal Distress being the leading indication for emergency Caesarean sections (30.00%). Conclusions: The study reveals the intricate challenges in managing pregnancies with uterine fibroids, highlighting potential risks, including spontaneous miscarriage. The emphasis on mode of delivery and detailed fibroid assessments offers valuable insights for clinicians navigating this complex patient population.